Strategies-Based English Instruction as a Method for Enhancing Reading Comprehension Skills in Higher Education Students - Sukarno, Sukarno; Dewi, Henda Harmantia; Saputro, Eko Prasetyo Nugroho; Priyana, Joko (Universitas Muhammadiyah Sidoarjo, 2024)
Reading comprehension skills are pivotal for the academic success and future careers of communication science students, making the use of effective teaching strategies essential for their development. This Classroom Action Research (CAR) investigates how Strategies-Based Instruction (SBI) improves students’ reading comprehension and overall learning experiences. Data were collected through observation, tests, and interviews, with quantitative analysis conducted using SPSS and qualitative analysis performed thematically. The results indicate that the implementation of SBI in reading classes increases students’ reading comprehension and positively influences aspects such as materials organization, student engagement, attitudes towards reading, and motivation to attend classes. Additionally, SBI promotes direct strategies that assist students master key skills, thereby better preparing them for their future careers. This study suggests that teachers should be equipped with both technological and pedagogical knowledge, through workshops or training, to improve their professionalism, particularly in teaching reading through the SBI framework. HIGHLIGHTS: SBI increases students’ reading comprehension. SBI Positively influences learning experiences. SBI promotes direct strategies that assist students master key skills for their futurecareers.